2011
DOI: 10.1523/jneurosci.6432-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Left Parietal Regions Are Critical for Adaptive Visuomotor Control

Abstract: The question addressed in this study is whether parietal brain circuits involved in adaptation to novel visuomotor conditions, are lateralized. This information is critical for characterizing the neural mechanisms mediating adaptive behavior in humans, as well as for assessing the effects of unilateral brain damage on function. Moreover, previous research has been controversial in this regard. We compared visuomotor adaptation in 10 patients with focal, unilateral, left or right parietal lesions and healthy co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
118
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(134 citation statements)
references
References 51 publications
(64 reference statements)
12
118
4
Order By: Relevance
“…Hemispheric specialization for different aspects of movement is also observed in adaptation tasks. Mutha et al (2011) compared visuomotor adaptation in patients with LH or RH lesions and observed adaptation only in those with an intact LH. Lefthand adaptation to prism displacement transfers to performance with the right, but right-hand adaptation does not transfer to the left hand Wallace 2008, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Hemispheric specialization for different aspects of movement is also observed in adaptation tasks. Mutha et al (2011) compared visuomotor adaptation in patients with LH or RH lesions and observed adaptation only in those with an intact LH. Lefthand adaptation to prism displacement transfers to performance with the right, but right-hand adaptation does not transfer to the left hand Wallace 2008, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Although this evidence inspired a departure from Liepmann's view of a comprehensively dominant left hemisphere, this change was only recently incorporated into theories of handedness (Carson 1993;Sainburg 2002). The view that each hemisphere may be specialized for different aspects of motor control has led to the understanding that unilateral hemisphere damage produces unique motor deficits that depend on the side of the lesion (Haaland and Flaherty 1984;Mani et al in press;Mutha et al 2011). Perhaps more importantly, hemisphere-specific deficits also occur in the ipsilesional arm of stroke patients, demonstrating that each hemisphere contributes different processes to control of each arm (Schaefer et al 2007(Schaefer et al , 2009.…”
mentioning
confidence: 99%
“…Other work has shown that damage or disruption of left, but not right, parietal cortex also disrupts 772 K.Y. Haaland et al motor adaptation (Della-Maggiore, Malfait, Ostry, & Paus, 2004;Mutha, Sainburg, & Haaland, 2011). This suggests that parietal cortex is critical not just for motor planning, but also for updating and maintaining new internal representations that are important for motor planning.…”
Section: Motor and Other Forms Of Learningmentioning
confidence: 99%